The CuO/ZnO and CuO/ZnO/biochar materials for water treatment - Lang J. (2020)
The research of new materials and methods for water treatment is necessary. Two sets of materials were prepared. The one set is composed from CuO/ZnO oxides with variable content of CuO and the second set consists of its biochar impregnated counterparts. The structure and phase composition was determined using X-ray diffraction method and morphology of the materials was studied using scanning electron microscopy. The photodegradation activity and adsorption properties were tested on model pollutant - Methylene blue (MB) dye solution. The experimental kinetic of the data was analyzed using pseudo-first-order and pseudo-second-order kinetic models and the equilibrium data was evaluated using Langmuir, Freundlich and Dubinin-Radushkievic models. It was found that optimal material for photodegradation of MB is 1% CuO/ZnO oxide and for the adsorption of MB is the best material raw corn cob biochar. © Published under licence by IOP Publishing Ltd.